Value of ultrasonography as a marker of early response to abatacept in patients with rheumatoid arthritis and an inadequate response to methotrexate: results from the APPRAISE study - D'Agostino, Maria-Antonietta (Ann Rheum Dis, 2016)
OBJECTIVES: To study the responsiveness of a combined power Doppler and greyscale ultrasound (PDUS) score for assessing synovitis in biologic-naïve patients with rheumatoid arthritis (RA) starting abatacept plus methotrexate (MTX). METHODS: In this open-label, multicentre, single-arm study, patients with RA (MTX inadequate responders) received intravenous abatacept (∼10 mg/kg) plus MTX for 24 weeks. A composite PDUS synovitis score, developed by the Outcome Measures in Rheumatology–European League Against Rheumatism (OMERACT–EULAR)-Ultrasound Task Force, was used to evaluate individual joints. The maximal score of each joint was added into a Global OMERACT–EULAR Synovitis Score (GLOESS) for bilateral metacarpophalangeal joints (MCPs) 2–5 (primary objective). The value of GLOESS containing other joint sets was explored, along with clinical efficacy. RESULTS: Eighty-nine patients completed the 24-week treatment period. The earliest PDUS sign of improvement in synovitis was at week 1 (mean change in GLOESS (MCPs 2–5): −0.7 (95% CIs −1.2 to −0.1)), with continuous improvement to week 24. Early improvement was observed in the component scores (power Doppler signal at week 1, synovial hyperplasia at week 2, joint effusion at week 4). Comparable changes were observed for 22 paired joints and minimal joint subsets. Mean Disease Activity Score 28 (C reactive protein) was significantly reduced from weeks 1 to 24, reaching clinical meaningful improvement (change ≥1.2) at week 8. CONCLUSIONS: In this first international prospective study, the composite PDUS score is responsive to abatacept. GLOESS demonstrated the rapid onset of action of abatacept, regardless of the number of joints examined. Ultrasound is an objective tool to monitor patients with RA under treatment. TRIAL REGISTRATION NUMBER: NCT00767325.